Peningkatan Kemampuan Administrasi dan Akuntansi dalam menghitung Biaya Kontrak pada Konsultan Perencana dan Pengawas Konstruksi di Surabaya - Marini Purwanto; Yustinus Budi Hemanto; Lindrawati (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Accounting is a practical science in its application in accordance with the specific applications and needs of each type of business entity. This community service activity is designed to provide assistance in preparing CV X's financial reports in the field of construction management consulting services that require progress reports on the progress of each contract. This community service activity is carried out by providing training to administrative staff so they can use Microsoft Excel from templates that have been made and guided by the community service team. Management expects that the output of this accounting information system can evaluate every ongoing project or project that has completed the contractual period. The output of this community service activity from this accounting information system is to accurately calculate the value of the cost of each project so that evaluation of the physical progress of the project and evaluation of the price and profitability analysis of each service contract can be carried out for monitoring and subsequent planning. The following evaluation needs follow-up to evaluate the application of PSAK 34 related to accounting for construction management consulting services.